(untitled) (Research, Society and Development, 2024)
The vegetable polymer was developed in order to have better performance in terms of diffusion-controlled release and porosity between the reactive natural phosphate P2O5 and the polymeric material. The biomaterial in question is an additive that forms a composite from biopolymerization. However, the economy of use and the release of Nitrogen, Carbon, Calcium, Phosphorus and Potassium are a source of mechanism route. According to Callister (2009), polymers are chains of monomers that are called oligomers. releasing Nitrogen in the form of adsorption and desorption for a controlled release. According to Fick’s law, reactions close to zero or greater than zero are considered non-chemical reactions. Chemical fractions without reactions.